1992
DOI: 10.1111/j.1476-5381.1992.tb14484.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac α1‐adrenoceptor densities in different mammalian species

Abstract: 1 ax-Adrenoceptor densities were studied in cardiac membrane preparations from several mammalian species including human failing hearts under identical experiment conditions; the al-adrenoceptor antagonist, [3H]-prazosin, was used as radioligand. End-stage heart failure (NYHA IV) in human hearts was due to idiopathic dilated cardiomyopathy. 2 The ventricular a1-adrenoceptor densities were not significantly different in guinea-pig, mouse, pig, calf, and man (11 to 18 fmol mg-' protein) but about 5 to 8 fold sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(33 citation statements)
references
References 26 publications
(23 reference statements)
2
29
0
2
Order By: Relevance
“…The number of cardiac α-and β-adrenergic receptors differs between rats and humans, 19,20 and such differences could have influenced the results of the present study. Therefore, we also need to examine the preventive effect of arotinolol in PAH patients.…”
Section: Study Limitationsmentioning
confidence: 54%
“…The number of cardiac α-and β-adrenergic receptors differs between rats and humans, 19,20 and such differences could have influenced the results of the present study. Therefore, we also need to examine the preventive effect of arotinolol in PAH patients.…”
Section: Study Limitationsmentioning
confidence: 54%
“…Although we already reported that noise exposure produces significant mitochondrial alterations in the rat myocardium (Soldani et al, 1997a,b), this is the first study investigating the effects of loud noise exposure on the mouse heart. This might be interesting, considering the similarities between mouse and human heart (Steinfath et al, 1992). The effects of noise exposure on mouse myocardium involve subcellular sites similar to those described in the rat (Paparelli et al, 1995;Pellegrini et al, 1996;Soldani et al, 1997a).…”
Section: Discussionmentioning
confidence: 88%
“…This higher sensitivity might be due to the zonal pattern of norepinephrine (NE) receptors (Gesi et al, 1999), which should be the final effectors for noise-induced myocardial alterations. In particular, rat myocardium possesses a high density of alpha-1 receptors in comparison with other mammalian species, such as mice or humans (Steinfath et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, among most species, including mouse, guinea pig, rabbit, pig, and cow, heart a 1 -AR levels determined by ligand binding are relatively constant (mouse: mean of six studies, ;12 fmol/mg protein) (Steinfath et al, 1992a;Cavalli et al, 1997;Yang et al, 1998;Lin et al, 2001;O'Connell et al, 2003;Rokosh and Simpson, 2002), with the exception of rat heart, in which a 1 -AR levels are approximately 10-fold higher (rat: mean of four studies, ;114 fmol/mg) (Steinfath et al, 1992a;Michel et al, 1994;Noguchi et al, 1995;Stewart et al, 1994).…”
Section: A a 1 -Adrenergic Receptor Expression In The Heart In Animamentioning
confidence: 99%